Fundamental parameters and non‐local thermodynamic equilibrium abundances of key light elements for nine bright and nearby K giants. Issue 3 (14th February 2021) - Lyubimkov, Leonid S.; Korotin, Sergey A.; Petrov, Dmitry V.; Poklad, Dmitry B.; Mkrtichian, David E.; Han, Inwoo; Lee, Byeong‐Cheol
Abstract: For nine bright K giants within 100 pc of the sun, the fundamental parameters and the non‐local thermodynamic equilibrium (LTE) abundances of three key light elements (Li, C, and O) are accurately determined. These stars are of special interest due to the planets detected around them. Their fundamental parameters are found to be typical for K giants; in particular, these stars have effective temperatures T eff = 3, 920–4, 830 K, surface gravities log g = 1.20–2.85, masses M = 1.2–2.8 M ⊙, and ages t = 0.4–5.4 Gyr (the pronounced anticorrelation between ages t and masses M exists). The microturbulent parameter V t derived from Fe I lines varies between 1.2 and 1.9 km s −1 ; the metallicity index [Fe/H] forfive stars is close to the normal (zero) value, for other four stars it varies between −0.3 and −0.4 dex. All the giants are on the red giant branch stage and passed the first‐dredge‐up (FDU) phase. This conclusion is confirmed by the published low isotope ratios 12 C/ 13 C and 16 O/ 17 O. Basing on the non‐LTE analysis of Li I, C I, and O I lines, we determined abundances of lithium, carbon, and oxygen, three tracers of stellar evolution. The carbon deficiency −0.3 dex is found for the giants, which is quite expectable for these post‐FDU objects. The oxygen abundance is likely to be unchanged, whereas for the C/O ratio we obtained (after correction due to galactic chemical evolution) the mean value [C/O]cor = −0.22 ± 0.10 that is in very good agreement with the theory. The lithium abundance is not detected for seven of nine program giants; this result is quite expectable for the post‐FDU stars. We determined the Li abundance with the confidence only for two giants, namely, log ϵ (Li) = 0.92 for β Gem and log ϵ (Li) = 0.45 for μ Leo; this result contradicts the standard theory. Hypothetical engulfment by a star of a giant planet could solve the problem.